LEADERSHIP IN HIGHER EDUCATION: ACADEMIC LEADER OR MANAGER? - Kurniawan, Agung Widhi; Puspitaningtyas, Zarah (Buletin Studi Ekonomi, 2013)
Higher education or college is an institution that gave birth to the intellectual resources expected to contribute in the human resources quality improving. All activities should be directed for the excellent academic performance. Management, especially university leaders, must start it from an awareness of the entire academic community. Awareness of university leaders should be depart from the philosophical, that not only manage the college-oriented economic capital (profit oriented), but also have socio-oriented capital. The question is what type of leadership that is appropriate to apply to higher education institutions in Indonesia? Leaders who have the spirit of academic leader or manager? Academic leaders must have the spirit of academic excellence, and is selected from the academics who have adequate leadership, communication, and interpersonal skills.
Keywords: leadership, higher education, academic leader, manager